The Influence of Brand Ambassador, Digital Marketing and Merchandise on Consumer Purchase Decisions on Blackpink Oreo Products - Fadlian Noor; Dito Aditia Darma Nasution (Future Science, 2022)
The spread of Hallyu or the Korean Wave (Korean wave) over the past few years has continued to increase. Korean wave or Hallyu has a variety of products ranging from K-dramas, films, music (K-pop), fashion and also food from South Korea which is now common among Indonesians. Currently, what is very popular among Indonesian people, from teenagers to adults, both women and men, from their teens to their tens, is K-Pop. K-pop has an important role in popularizing the Korean wave in Indonesia. This study uses a quantitative method using a questionnaire in the form of google form as the instrument. The population in this study are BLINKs who have purchased Oreo x Blackpink products. The sample in this study used non-probability sampling with purposive sampling of 96 respondents. The data analysis technique in this study is Instrument Test, classical assumption test, multiple linear regression, determination test and hypothesis testing. The results of this research show that together the independent variables have an influence on purchasing decisions.